Working with lathes - Safetycare Australia (Firm) (Australia : Safetycare Australia, 1992)
This program covers the safe and correct use of the lathe. It includes: Workshop and operator safety; Identification, correct use and maintenance of all components which make up the lathe, including the carriage, headstock, tailstock, cross-slide, top-slide and compound rest; Correct procedure for changing the spindle speed; Step by step instruction on correct centring and mounting of workpieces; Setting up the cutting tool and adjustrment of the cutting speed and feed; How to make rough and finish cuts
Title from title screen
VCD format
Keywords: Industrial safety; Lathes -- Maintenance and repair